Absence of carcinogenic and anticarcinogenic effects of annatto in the rat liver medium-term assay - Agner, A. R.; Barbisan, Luis Fernando [UNESP]; Scolastici, C.; Salvadori, Daisy Maria Favero [UNESP] (Elsevier B.V., 2004)
Annatto (Bixa orellana L.) is a natural food colorant extensively used in many processed foods, especially dairy products. The lower cost of production and the low toxicity, make annatto a very attractive and convenient pigment in substitution to the many synthetic colorants. In the present study we investigate the carcinogenic and anticarcinogenic effects of dietary annatto in Wistar rat liver using the preneoplastic glutathione S-transferase (GST-P) foci and DNA damage biomarkers. Annatto, containing 5% bixin, was administered in the diet at concentrations of 20, 200, and 1000 ppm (0.07; 0.80 and 4.23 bixin/kg body wt/day, respectively), continuously during 2 weeks before, or 8 weeks after DEN treatment (200 mg/kg body wt, i.p.), to evaluate its effect on the liver-carcinogenesis medium-term bioassay. The comet assay was used to investigate the modifying potential of annatto on DEN (20 mg/kg body wt)-induced DNA damage. The results showed that annatto was neither genotoxic nor carcinogenic at the highest concentration tested (1000 ppm). No protective effects were also observed in both GST-P foci development and comet assays. In conclusion, in such experimental conditions, annatto shows no hepatocarcinogenic effect or modifying potential against DEN-induced DNA damage and preneoplastic foci in the rat liver. (C) 2004 Elsevier Ltd. All rights reserved.
Keywords: annatto; carcinogenesis; chemoprevention; diethylnitrosamine; genotoxicity; GST-P positive foci; comet assay